2015
DOI: 10.1126/scitranslmed.aab2354
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to influenza nucleoprotein cross-react with human hypocretin receptor 2

Abstract: The sleep disorder narcolepsy is linked to the HLA-DQB1*0602 haplotype and dysregulation of the hypocretin ligand-hypocretin receptor pathway. Narcolepsy was associated with Pandemrix vaccination (an adjuvanted, influenza pandemic vaccine) and also with infection by influenza virus during the 2009 A(H1N1) influenza pandemic. In contrast, very few cases were reported after Focetria vaccination (a differently manufactured adjuvanted influenza pandemic vaccine). We hypothesized that differences between these vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
200
4
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(213 citation statements)
references
References 73 publications
3
200
4
6
Order By: Relevance
“…[10][11][12] In addition, the surge of cases of narcolepsy following pandemic H1N1 infection and mass vaccination with Pandemrix (GlaxoSmithKline, Brentford, Middlesex, UK) lends further support to an autoimmune etiology, [13][14][15][16] likely due to serum antibodies to H1N1 nucleoprotein in patients with vaccine-associated narcolepsy cross-reacting with the hypocretin receptor 2 (an effect observed following Pandremix, but not Focetria [Novartis, Novartis International AG, Basel, Switzerland] vaccination). 17 However, in the absence of formal identification and detailed understanding of the mechanisms linking autoimmunity with the destruction of hypocretin neurons, no disease-modifying therapies for narcolepsy have yet been developed.…”
mentioning
confidence: 99%
“…[10][11][12] In addition, the surge of cases of narcolepsy following pandemic H1N1 infection and mass vaccination with Pandemrix (GlaxoSmithKline, Brentford, Middlesex, UK) lends further support to an autoimmune etiology, [13][14][15][16] likely due to serum antibodies to H1N1 nucleoprotein in patients with vaccine-associated narcolepsy cross-reacting with the hypocretin receptor 2 (an effect observed following Pandremix, but not Focetria [Novartis, Novartis International AG, Basel, Switzerland] vaccination). 17 However, in the absence of formal identification and detailed understanding of the mechanisms linking autoimmunity with the destruction of hypocretin neurons, no disease-modifying therapies for narcolepsy have yet been developed.…”
mentioning
confidence: 99%
“…The tight association between narcolepsy and HLA subtypes and other genes involved in autoimmunity (10,11) has provided the framework for most research on the connection between narcolepsy and infectious agents (12). Indeed, a recent study found that sera from HLA-DQB1*0602-positive patients with Pandemrix-associated narcolepsy contained antibodies that cross-reacted with the H1N1 nucleoprotein and the HCRT receptor 2 (13). But whether the H1N1 virus itself, without mechanisms of molecular mimicry or other means of induced autoimmunity, can infect neurons that regulate arousal state and cause functional changes akin to narcolepsy has not been addressed-until now.…”
Section: Narcolepsy: Autoimmunity Vs Direct Viral Infectionmentioning
confidence: 99%
“…The main graded exercise in the course on the brain and the immune system that I taught vaccines and mimics the receptor for orexin in the brain. The orexin receptor is intimately involved in sleep and feeding behavior (14). The intersection of the brain and the immune system, and the genetic control of the immune response apparently recurs in my life in research.…”
Section: Write and Communicatementioning
confidence: 99%
“…Fifty years later, I returned to the same subject, this time in humans, who developed a neurologic disease after influenza immunization, but only when they had certain genetic backgrounds (14).…”
Section: Medical School and Postdoctoral Studiesmentioning
confidence: 99%
See 1 more Smart Citation